Análisis y diseño de una aplicación web para promocionar las huecas de comidas de pequeños negocios del cantón de Quevedo año 2016 - Chicaiza Romero, Mónica Gabriela (2016)
In this research has been done, a web application addressed to the business of food or better known as hollow or agachaditos Cantón Quevedo. With the purpose that they are promoting their services on the internet and that lack of knowledge in regard to advertising in online media is not limiting. Furthermore, it is expected that with the implementation of the web application on the part of the department of tourism businesses increase the number of customers and streamline further the tourism in the Canton Quevedo. For the research project used data collection techniques known as are the interview and survey, which was detected are the main hollow food. For the development of the software will work with the Agile Scrum methodology. A Isologo that identifies the web application and its hollow. In addition to used the image editing program Adobe Photoshop to try and touch up the images of the dishes of the hollow. In Quevedo there are a large number of hollow that have many years of experience and are already established in the market, but lack a proper advertising because many of them do not have a label identifying them from the competition rather are identified by being the only ones who expend such a variety of dishes. Therefore the methodology Scrum is the make the most when working in groups of older people to five because the workload is shared between the team, as well as to work a person the load is greater with Scrum, but the performance of the work is better.